The Family of Francis Marion Shaw Newsletter Volume 6 Number 2 - Shaw, Bryan Lee (My University, 1997)
This newsletter focuses on the life of Francis Marion Shaw, a Confederate veteran who lost his right arm in a skirmish at Cedar Keys, Florida, in 1864. Despite being gaunt from his trauma, he returned home to clear and cultivate land acquired from his father. In 1866, he married Rachel Moore Allen, a widow ten years his senior with three children, their shared losses bringing them together. In 1867, Shaw, along with his father and brother, signed an Oath of Allegiance to the United States as required by the First Reconstruction Act, with Francis Marion Shaw making an "x" mark due to the loss of his writing arm.
This item has 1 PDF file with 4 pages and a title page in addition to 4 JP2 files.
Keywords: Berrien County Historical Foundation (Nashville; Ga.); Nashville (Ga.); Berrien County (Ga.); Newsletters; Periodicals; Berrien County (Ga.)--History--Sources; Electronic records; Grady County (Ga.)--History; Historic preservation--Georgia--Berrien County; Georgia--Genealogy